2020
DOI: 10.1021/acs.organomet.9b00801
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Photocatalytic CO2 Reduction by a Ni(II) Complex Bearing an S2N2-Type Ligand

Abstract: Photocatalytic CO2 reduction to CO by a Ni­(II) complex with an S2N2-type tetradentate ligand exhibits high efficiency and selectivity. Here, a density functional theory (DFT) study of the reaction mechanism is presented. Our calculations support that the four-coordinated Ni0 species formed through a photoinduced process participates in the actual catalytic reaction, which reduces CO2 to CO and then regenerates the NiII species. A CO2 adduct with the η2 CO binding mode is the precursor for the formation of CO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…These ligands are also found in combination with carbonyl or halogen ligands [78] . It is also common to find complexes with a coordination position occupied by a labile solvent molecule that can be readily exchanged by the carbon dioxide substrate [63,76,79,80] …”
Section: General Description Of Molecular Catalytic Systems Used For ...mentioning
confidence: 99%
See 3 more Smart Citations
“…These ligands are also found in combination with carbonyl or halogen ligands [78] . It is also common to find complexes with a coordination position occupied by a labile solvent molecule that can be readily exchanged by the carbon dioxide substrate [63,76,79,80] …”
Section: General Description Of Molecular Catalytic Systems Used For ...mentioning
confidence: 99%
“…Recently Chen's group published a study [80] of the CO 2 reduction catalysed by a Ni complex containing an uncommon tetradentate ligand of type S 2 N 2 , the [Ni( pmet )X 2 ] 2+ ( pmet =bis(2‐pyridylmethyl)‐1,2‐ethanethiol, X=acetonitrile, 13 , Scheme 7). The experimental study [66] was performed using a photocatalytic system formed by the Ni(II) complex, PS2 as photosensitiser and BIH as an electron donor.…”
Section: Mechanistic Studies Of Catalytic Photoreduction Of Co2mentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism has been discussed by Chen and coworkers using DFT calculations to gain mechanistic insights into the CO formation using 14. [28] Addition of a Lewis acid to the reaction solution for electrochemical CO 2 reduction has been reported to exhibit positive impact on the reaction. [29][30][31][32][33] For example, it has been demonstrated that the presence of Mg 2 + ions enhances the electrochemical CO 2 reduction using a Mn complex as a catalyst in terms of the higher rate of catalysis and lower overpotential.…”
Section: Ni Complexes With Sulfur-containing Ligandsmentioning
confidence: 99%